PENGARUH GAYA HIDUP, RELIGIUSITAS, FINANCIAL TECHNOLOGY, DAN LOCUS OF CONTROL TERHADAP PERILAKU KEUANGAN MAHASISWA - Feriz, Naufal Jabsy; Ariani, Kurnia Rina (JURNAL ILMIAH EDUNOMIKA, 2025)
Financial management is important to take into account all forms of expenses made by each individual. The increase in human needs, consumptive attitudes, and high lifestyles cause some individuals to not realize that they have spent their money without any calculation. Religious values ultimately have an influence on the attitude and behavior of individuals in making decisions on the choices they face, including in terms of individual financial management. The presence of financial technology facilitates the access and use of financial services by the community, especially students. The locus of control can affect an individual's financial behavior as it relates to how an individual takes responsibility for managing his or her finances. This study uses a quantitative research method with the calculation of a sample of the convenience method of 300 respondents. Validity and reliability tests on instruments are confirmed to be valid and reliable. The findings of this study reveal that lifestyle, religiosity and financial technology significantly affect financial behavior. Then the locus of control does not have a significant influence on financial behavior. Furthermore, it was proven that there was no difference in financial behavior between students of the University of Muhammadiyah Surakarta and students of Sebelas Maret University, meaning that there was no difference in financial behavior between students of private universities and public universities in Surakarta